Implementation of Web Inventory Tracking and Monitoring for PT Sucofindo Samarinda Branch: Implementasi Web Inventory Tracking dan Monitoring untuk PT Sucofindo Cabang Samarinda - Chitta Putra Rihesvar Krishna; Muhammad Zainul Rohman; Bambang Cahyono (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Logistics is a role in the corporate world that discusses the distribution flows management, maintenance, and storage of goods or materials. PT Sucofindo Samarinda Branch as a service company in the field of testing, inspection, and certification in various sectors requires a goods management website in order to adapt to the digital era. This need arises from user problems such as the difficulty of monitoring the flow of goods in real time, limited information on available goods, and the inefficiency of manual submission of goods. This company requires several functions on the web, starting from the ability to accommodate various types of goods information, monitor the movement and management of goods, track the position and quantity of goods, and to apply for permission to use or request goods from branches. The initial design of this web system was designed using Figma, then the design was built using Adobe Dreamweaver based on the Conceptual Data Model (CDM) diagram. The web also includes a database using PHPMyAdmin and Xampp to connect the web database without connecting to the web server, and implementing the entire system into the CodeIgniter framework. This system works as an information center in storing important data with a comfortable, simple, and clear UI design to improve the efficiency of supply chain management. Although web-based, human involvement is still the main element in providing accurate monitoring and periodic tracking. This activity provides a comprehensive solution to improve the quality of the goods management process at PT Sucofindo Samarinda Branch.